Male privileging and male 'academic underperformance' in Jamaica - Figueroa, Mark (UWI Press, 2004)
This chapter seeks to ascertain the extent to which male academic underperformance can be understood in relation to the historical privileging of males, using Jamaica as a case study. Instead of seeing the current underperformance as a result of male marginalization or victimization, the chapter demonstrates how it might be conceptualized as an ironic consequence of historic male privileging. The chapter begins with an examination of some of the statistical evidence available and demonstrates that, although females are often outperforming males in terms of overall numbers, a more detailed analysis of the statistics reveals the footprint of the old male privileging. It then seeks to show how the increasing tendency of males to lose ground in academic fields where they had previously dominated can be seen as part of a process of cumulative causation in which cultural patterns rooted in the historical privileging of the male gender play an important part. The chapter further interrogates the gendered processes that are taking place in the schoolroom and seeks to show that these may be contributing to male underperformance, and also examines the impact of motivational and other factors beyond the school gate. It concludes by indicating how transformation of gender relations and the reform of the educational system might benefit all concerned and provides some suggestions for further research.
Editor: Rhoda Reddock
Keywords: Male underachievement